Preoperative nutritional risk assessment in patients undergoing cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy for colorectal carcinomatosis. (4th July 2018) - Banaste, Nathan; Rousset, Pascal; Mercier, Frederic; Rieussec, Clémentine; Valette, Pierre-Jean; Glehen, Olivier; Passot, Guillaume
Abstract: Background: Malnutrition is associated with increased postoperative morbidity in colorectal surgery. This study aimed to determine if preoperative nutritional markers could predict postoperative outcomes for patients undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) for peritoneal metastasis (PM) of colorectal origin. Methods: All patients who underwent a complete CRS-HIPEC for colorectal PM between January 2009 and December 2014 were evaluated. Preoperative clinical and biological nutritional factors, including Body Mass Index (BMI), preoperative albumin and prealbumin levels were analysed. Preoperative computed tomography was used to measure the cross-sectional surface of the visceral and subcutaneous adipose tissue, at the third lumbar vertebrae, to assess the abdominal fat composition. Skeletal muscle mass was measured to assess for sarcopenia. Results: Among 214 patients, 14 (6.5%) had a BMI ≥ 35 kg/m 2, 90 (42%) were sarcopenic, 19 (9%) presented albumin <35 g/L and 2 (1%) had pre-albumin <20 mg/dL. Median values for visceral and subcutaneous fat surfaces were 99.2 cm 2 and 198 cm 2, respectively. Hypoalbuminemia was associated with worse overall survival (23 vs. 59 months, p = 0.015). The other nutritional factors did not impact overall or progression free survival after CRS-HIPEC for colorectal PM. In multivariate analysis, major post-operative complication and hypoalbuminemia were independently associated with decreased overall survival. Conclusions: Hypoalbuminemia appears as a strong predictive factor for decreased overall survival in patients presenting PM of colorectal origin undergoing CRS-HIPEC.